Elecrtical treeing performance of silicone rubber nanocomposites treated with plasma and silane coupling [electronic resource] - Mohamad Naquib Morsin, 1993-, author (2016)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2016